2022
DOI: 10.3389/fvets.2022.911166
|View full text |Cite
|
Sign up to set email alerts
|

Deep Small RNA Sequencing Reveals Important miRNAs Related to Muscle Development and Intramuscular Fat Deposition in Longissimus dorsi Muscle From Different Goat Breeds

Abstract: MicroRNAs (miRNAs) are a class of small non-coding RNAs that have been shown to play important post-transcriptional regulatory roles in the growth and development of skeletal muscle tissues. However, limited research into the effect of miRNAs on muscle development in goats has been reported. In this study, Liaoning cashmere (LC) goats and Ziwuling black (ZB) goats with significant phenotype difference in meat production performance were selected and the difference in Longissimus dorsi muscle tissue expression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 70 publications
0
8
0
Order By: Relevance
“…In this context, SMSCs have been widely used as models for investigating the growth and development of skeletal muscle in various species [ 3 , 4 , 6 , 7 ]. In our previous study, miR-381 was identified as the most down-regulated miRNA (fold change = 20.0, p = 1.6 × 10 −8 ) in Liaoning cashmere goats with higher muscle fiber size and carcass weight compared to Ziwuling black goats [ 10 ]. It was therefore inferred that miR-381 may regulate the size of caprine muscle fiber by regulating the activities of SMSCs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, SMSCs have been widely used as models for investigating the growth and development of skeletal muscle in various species [ 3 , 4 , 6 , 7 ]. In our previous study, miR-381 was identified as the most down-regulated miRNA (fold change = 20.0, p = 1.6 × 10 −8 ) in Liaoning cashmere goats with higher muscle fiber size and carcass weight compared to Ziwuling black goats [ 10 ]. It was therefore inferred that miR-381 may regulate the size of caprine muscle fiber by regulating the activities of SMSCs.…”
Section: Discussionmentioning
confidence: 99%
“…In our previous study, miR-381 was found to be the most down-regulated miRNA in skeletal muscle of Liaoning cashmere goats with higher meat yield and larger muscle fiber size, when compared to Ziwuling black goats [ 10 ]. For example, the carcass weight of Liaoning cashmere goats was 14.10 ± 1.17 kg, which was higher than that of Ziwuling black goats with a carcass weight of 7.45 ± 1.28 kg.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that in the postnatal period of animals, increases of skeletal muscle mass mainly depend on the hypertrophy of muscle fibers, closely related to proliferation and differentiation of SMSCs [ 42 , 43 , 44 , 45 ]. In this study, si-circ_003628 decreased the expression levels of proliferation marker genes Pax7 , CDK2 , CDK4 and CyclinD1 .…”
Section: Discussionmentioning
confidence: 99%
“…The miRNA raw data were processed through an in-house program, ACGTA101-miR (v4.2) (LC Science, USA) to remove adapter dimers, junk, low complexities, common RNA families (rRNA, tRNA, snRNA, and snoRNA), repeats, and sequences <18 nt or >26 nt in length were filtered out using Rfam (v13.0) and Repbase Update ( 28 , 29 ). The 18~26 nt unique reads were mapped to miRNA sequences in miRBase (v22.0) ( 30 ). Mapping was also performed on pre-miRNA against Ovis aries genomic data (GCA_000298735.1).…”
Section: Methodsmentioning
confidence: 99%
“…Mapping was also performed on pre-miRNA against Ovis aries genomic data (GCA_000298735.1). The unique sequences that aligned to the known miRNA sequences in miRBase (v22.0) were identified as known miRNAs ( 30 ). The secondary structure of pre-miRNAs was presented as a hairpin, including 5p- and 3p- derived miRNA.…”
Section: Methodsmentioning
confidence: 99%